Jane Austen's lifelong health problems and final illness: New evidence points to a fatal Hodgkin's disease and excludes the widely accepted Addison's. Issue 1 (15th June 2005) - Upfal, A
Abstract : Jane Austen is typically described as having excellent health until the age of 40 and the onset of a mysterious and fatal illness, initially identified by Sir Zachary Cope in 1964 as Addison's disease. Her biographers, deceived both by Cassandra Austen's destruction of letters containing medical detail, and the cheerful high spirits of the existing letters, have seriously underestimated the extent to which illness affected Austen's life. A medical history reveals that she was particularly susceptible to infection, and suffered unusually severe infective illnesses, as well as a chronic conjunctivitis that impeded her ability to write. There is evidence that Austen was already suffering from an immune deficiency and fatal lymphoma in January 1813, when her second and most popular novel, Pride and Prejudice, was published. Four more novels would follow, written or revised in the shadow of her increasing illness and debility. Whilst it is impossible now to conclusively establish the cause of her death, the existing medical evidence tends to exclude Addison's disease, and suggests there is a high possibility that Jane Austen's fatal illness was Hodgkin's disease, a form of lymphoma.